2005
DOI: 10.1103/physrevlett.95.187001
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Nernst Effect in the Metallic and Field-Induced Spin Density Wave States of(TMTSF)2ClO4

Abstract: We examine an unusual phenomenon where, in tilted magnetic fields near magic angles parallel to crystallographic planes, a "giant" resonant Nernst signal has been observed by Wu et al.[Phys. Rev. Lett. 91 56601(2003)] in the metallic state of an organic conducting Bechgaard salt. We show that this effect appears to be a general feature of these materials, and is also present in the field induced spin density wave phase with even larger amplitude. Our results place new restrictions on models that treat the meta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…The signal is consistent with 2D conducting planes originating from an orbital resonance of motion along the field direction at the MA distinct from the molecular ab plane. This measurement not only sheds new light on previously unresolved Lebed resonance behavior [13,14] but also establishes the emergence of an orbital resonance-driven Hall effect and an emergent low-dimensional system ripe for further exploration.Most commonly, the MA effect is observed as a dip structure in the interlayer resistance R zz as a function of angle θ at the MA condition defined aswhere b and c are lattice constants in the y and z direction, p and q are integers, and θ is measured from the z axis. A microscopic and macroscopic depiction of the crystal are shown inset in Fig.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The signal is consistent with 2D conducting planes originating from an orbital resonance of motion along the field direction at the MA distinct from the molecular ab plane. This measurement not only sheds new light on previously unresolved Lebed resonance behavior [13,14] but also establishes the emergence of an orbital resonance-driven Hall effect and an emergent low-dimensional system ripe for further exploration.Most commonly, the MA effect is observed as a dip structure in the interlayer resistance R zz as a function of angle θ at the MA condition defined aswhere b and c are lattice constants in the y and z direction, p and q are integers, and θ is measured from the z axis. A microscopic and macroscopic depiction of the crystal are shown inset in Fig.…”
mentioning
confidence: 93%
“…The signal is consistent with 2D conducting planes originating from an orbital resonance of motion along the field direction at the MA distinct from the molecular ab plane. This measurement not only sheds new light on previously unresolved Lebed resonance behavior [13,14] but also establishes the emergence of an orbital resonance-driven Hall effect and an emergent low-dimensional system ripe for further exploration.…”
mentioning
confidence: 93%
“…The giant Nernst resonances and giant Nernst effect have also been observed in the sister compound ͑TMTSF͒ 2 ClO 4 . 23,24 Both the sign change at the magic angles and the large magnitude of the signal are not yet explained, but the effect appears generic for these materials. Any theoretical description of the magic angle effect should explain both resistivity dips and the resonantlike Nernst effect.…”
mentioning
confidence: 99%
“…[21][22][23] It has been shown that the Boltzmann transport fails to explain the resonantlike Nernst effect at magic angles and their giant magnitude, when there is no magnetic field component along the a axis ͓B x = 0 curve in Fig. 2͑a͔͒.…”
mentioning
confidence: 99%
“…On the other hand, in many cases, the LMA phenomena are experimentally claimed [9-13] to be of a nonFermi-liquid nature. This was claimed by Chaikin's group for the Nernst effect in (TMTSF) 2 PF 6 [9,10,12], by Brooks' group for the Nernst effect in (TMTSF) 2 ClO 4 [11], and recently by Uji's group [13] for the Hall effect in (TMTSF) 2 ClO 4 . In our opinion, some non-Fermi-liquid effects were also observed in the LMA resistive experiments in the Q1D compound (Per) 2 Au(mnt) 2 by Graf et al [14].…”
mentioning
confidence: 88%